Anisotropic conductive nano composite material as well as preparation method and application thereof
By super-spreading two-dimensional nanosheets on the surface of the liquid film and performing oxidation polymerization, anisotropic conductive nanocomposites were prepared, which solved the problem of conducting polymer materials achieving different conductivity in different directions, and achieved the efficient conductivity and mechanical properties of the materials.
Patent Information
- Application Number
- CN202510387057.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-31
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2045-03-31
AI Technical Summary
Existing conductive polymer materials have difficulty achieving different conductivity in different directions and cannot meet the specific working conditions of certain electronic and optoelectronic applications.
Anisotropic conductive nanocomposite materials are prepared by super-spreading two-dimensional nanosheets on the surface of the liquid film to form a nano-confined space, and the conductive polymer monomer and the oxidizing agent are oxidized and polymerized.
The conductivity differences of conductive polymer materials in different directions are achieved, the conductive and mechanical properties of the materials are enhanced, and the stability and reliability of the materials are improved.
Smart Images

Figure CN119899411A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of conductive materials, and in particular relates to an anisotropic conductive nanocomposite material and a preparation method and application thereof. Background Art
[0002] Conductive polymers refer to polymers with good electrical conductivity. Common conductive polymers include polyaniline (PANI), polypyrrole (PPy), poly(3,4-ethylenedioxythiophene) (PEDOT), etc. Compared with traditional metal conductors, conductive polymers not only have light weight and good flexibility, but are also easy to process and mold, and are suitable for various electronic and optoelectronic applications. With the development of flexible electronics, wearable devices and smart materials, anisotropic conductive polymers are becoming increasingly important because they can meet the stringent requirements of these cutting-edge fields for material functionality and performance. In some applications, such as sensors and flexible circuits, the conductivity of conductive polymer materials in different directions must meet different standards to meet specific working conditions, but how to achieve different conductivity of conductive polymer materials in different directions remains to be studied. Summary of the invention
[0003] In view of the above technical problems, the present invention provides an anisotropic conductive nanocomposite material and a preparation method and application thereof, in order to at least partially solve the above technical problems. The specific technical solutions provided by the present invention are as follows.
[0004] As a first aspect of the present invention, a method for preparing an anisotropic conductive nanocomposite material is provided, comprising: applying a first mixed solution containing metal ions and an oxidant on a substrate having a lyophilic surface to form a liquid film on the lyophilic surface; pouring a second mixed solution formed by uniformly mixing a conductive polymer monomer with a two-dimensional nanosheet dispersion onto the surface of the liquid film and allowing the mixture to stand for a period of time, wherein the two-dimensional nanosheets are super-spread on the surface of the liquid film and form nano-confined spaces between adjacent two-dimensional nanosheets, and within the nano-confined spaces, the conductive polymer monomer and the oxidant undergo an oxidative polymerization reaction to obtain a composite film; and drying the composite film to obtain an anisotropic conductive nanocomposite material.
[0005] As a second aspect of the present invention, an anisotropic conductive nanocomposite material is provided, which is prepared by the above method.
[0006] As a third aspect of the present invention, there is provided an application of an anisotropic conductive nanocomposite material in an electronic device.
[0007] In an embodiment of the present invention, a nano-confined space is formed by super-spreading a two-dimensional nanosheet on the surface of a liquid film, so that a conductive polymer monomer undergoes an oxidative polymerization reaction therein, and this special structure is conducive to the formation of an anisotropic conductive channel. At the same time, the reaction environment in the nano-confined space is relatively stable and uniform, which is conducive to the uniform polymerization of the conductive polymer monomer between the two-dimensional nanosheets, so that the anisotropic conductive nanocomposite material (hereinafter referred to as the composite material) finally obtained has good uniformity at the nanoscale. The introduction of two-dimensional nanosheets not only contributes to the conductive properties, but also enhances the mechanical properties of the composite material. The composite structure formed by the two-dimensional nanosheet and the conductive polymer monomer can improve the overall strength and toughness of the composite material, so that the composite material can better withstand external forces and environmental changes in practical applications, is not prone to rupture or damage, and improves the stability and reliability of the composite material. The preparation method of the anisotropic conductive nanocomposite material provided by the present invention mainly includes operations such as mixing solutions, pouring, and standing, does not require complex equipment and advanced technology, is easy to implement and control, reduces the preparation cost and technical threshold, and is conducive to large-scale production and application. The composite material is directly reacted on the liquid film surface of the substrate, without the need for additional complex assembly or transfer processes, reducing the problems of impurity introduction and structural damage that may be caused by the intermediate links, which is conducive to maintaining the integrity and performance of the composite material. At the same time, the in-situ generation method also improves the preparation efficiency and shortens the preparation cycle. BRIEF DESCRIPTION OF THE DRAWINGS
[0008] Figure 1 is a flow chart of a method for preparing anisotropic conductive nanocomposite materials in an embodiment of the present invention;
[0009] Figure 2 This is a flow chart of the preparation of the anisotropic conductive nanocomposite material in Example 1 of the present invention;
[0010] Figure 3 This is a scanning electron microscope image of the anisotropic conductive nanocomposite material in Example 1 of the present invention at a magnification of 5000×;
[0011] Figure 4 is a scanning electron microscope image of the anisotropic conductive nanocomposite material in Example 1 of the present invention at a magnification of 10000×;
[0012] Figure 5 This is a transmission electron microscope image of the anisotropic conductive nanocomposite material in Example 1 of the present invention;
[0013] Figure 6 is an X-ray diffraction pattern of the anisotropic conductive nanocomposite material in Example 1 of the present invention;
[0014] Figure 7is an X-ray diffraction pattern of the anisotropic conductive nanocomposite material in Example 5 of the present invention;
[0015] Figure 8 It is a schematic diagram of the conductivity test in the horizontal direction in an embodiment of the present invention;
[0016] Fig. 9 Schematic diagram of conductivity test in the vertical direction in an embodiment of the present invention.
[0017] Description of reference numerals:
[0018] 1-liquid film; 2-oxidant; 3-metal ions; 4-conductive polymer monomer; 5-two-dimensional nanosheet. DETAILED DESCRIPTION
[0019] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments and with reference to the accompanying drawings.
[0020] The anisotropic conductive properties of conductive polymers can be achieved through the arrangement, orientation or doping of materials, so that composite materials with specific conductive properties can be designed. This functionalization provides new opportunities for the development of adaptive and multifunctional materials. However, the conductive mechanism of anisotropic conductive materials still needs to be further studied, especially how to optimize the structure and composition of the material to enhance its anisotropy.
[0021] Based on this, the present invention provides an anisotropic conductive nanocomposite material and its preparation method and application. Using a super-spreading strategy, a conductive polymer monomer is mixed with a two-dimensional nanosheet dispersion, and super-spread on a substrate with a lyophilic surface that has been soaked in a metal ion and oxidant solution, a nano-confined space is formed between adjacent two-dimensional nanosheets, and the conductive polymer monomer undergoes chemical oxidation polymerization with the oxidant in the nano-confined space, thereby obtaining an anisotropic conductive nanocomposite material.
[0022] Figure 1 The flowchart is a method for preparing anisotropic conductive nanocomposite materials in an embodiment of the present invention.
[0023] As a first aspect of the present invention, a method for preparing an anisotropic conductive nanocomposite material is provided, such as Figure 1 As shown, steps S1-S3 are included.
[0024] S1: applying a first mixed solution containing metal ions and an oxidant on a substrate having a lyophilic surface to form a liquid film on the lyophilic surface.
[0025] S2: Pour a second mixed liquid formed by uniformly mixing the conductive polymer monomer and the two-dimensional nanosheet dispersion onto the surface of the liquid film and let it stand for a period of time, wherein the two-dimensional nanosheets super-spread on the surface of the liquid film and form nano-confined spaces between adjacent two-dimensional nanosheets. In the nano-confined spaces, the conductive polymer monomer and the oxidant undergo oxidative polymerization reaction to obtain a composite film.
[0026] S3: Drying the composite film to obtain an anisotropic conductive nanocomposite material.
[0027] In an embodiment of the present invention, a nano-confined space is formed by super-spreading a two-dimensional nanosheet on the surface of a liquid film, so that a conductive polymer monomer undergoes an oxidative polymerization reaction therein, and this special structure is conducive to the formation of an anisotropic conductive channel. At the same time, the reaction environment in the nano-confined space is relatively stable and uniform, which is conducive to the uniform polymerization of the conductive polymer monomer between the two-dimensional nanosheets, so that the composite material finally obtained has good uniformity at the nanoscale. The introduction of two-dimensional nanosheets not only contributes to the conductive properties, but also enhances the mechanical properties of the composite material. The composite structure formed by the two-dimensional nanosheet and the conductive polymer monomer can improve the overall strength and toughness of the composite material, so that the composite material can better withstand external forces and environmental changes in practical applications, is not prone to rupture or damage, and improves the stability and reliability of the composite material. The preparation method of the anisotropic conductive nanocomposite material provided by the present invention, the entire preparation process mainly includes operations such as mixing solutions, pouring, and standing, does not require complex equipment and advanced technology, is easy to implement and control, reduces the preparation cost and technical threshold, and is conducive to large-scale production and application. The composite material is directly reacted on the liquid film surface of the substrate, without the need for additional complex assembly or transfer processes, reducing the problems of impurity introduction and structural damage that may be caused by the intermediate links, which is conducive to maintaining the integrity and performance of the composite material. At the same time, the in-situ generation method also improves the preparation efficiency and shortens the preparation cycle.
[0028] According to an embodiment of the present invention, the two-dimensional nanosheets are super-spread on the surface of the liquid film and form a nano-confined space between adjacent two-dimensional nanosheets, including: the two-dimensional nanosheets are super-spread on the surface of the liquid film and oriented in a first direction, and then the metal ions are cross-linked and cured with the two-dimensional nanosheets to form a nano-confined space between adjacent two-dimensional nanosheets in a second direction; wherein the first direction is parallel to the substrate and the second direction is perpendicular to the substrate. The two-dimensional nanosheets spread rapidly on the surface of the liquid film at an extremely fast speed (the time required is less than or equal to 2s) and an extremely low contact angle (approaching 0), quickly covering the surface of the liquid film, and forming a state of uniform distribution and orderly arrangement. The cross-linking and curing effect of the metal ions and the two-dimensional nanosheets enhances the bonding force between the two-dimensional nanosheets, making the structure of the composite material more stable.
[0029] According to an embodiment of the present invention, the metal ion is selected from at least one of iron ions, calcium ions, and aluminum ions. Iron ions, calcium ions, and aluminum ions all have multiple coordination sites, which can cross-link with the functional groups on the surface of the two-dimensional nanosheets, so that the two-dimensional nanosheets form a stable nanoconfined space in the second direction. Different metal ions can give different properties to the composite material. Iron ions have certain magnetism, and the introduction of iron ions can make the composite material have certain magnetic response performance, which can be applied to the field of magnetic control; calcium ions have biocompatibility, and the introduction of calcium ions in composite materials used in the biomedical field helps to improve the compatibility of materials with biological tissues; aluminum ions can improve the mechanical strength of materials, making composite materials more durable.
[0030] According to an embodiment of the present invention, the oxidant is selected from at least one of hydrogen peroxide, dichromate, persulfate, and ferric chloride. The oxidant can provide an oxidizing environment to initiate an oxidative polymerization reaction of the conductive polymer monomer. Different oxidants have different oxidizing abilities and reactivity, and the degree of polymerization of the conductive polymer monomer can be accurately controlled by selecting a suitable oxidant and controlling its dosage.
[0031] According to an embodiment of the present invention, the concentration of metal ions in the first mixed solution is 0.2-3 mol / L. Within this concentration range, it is possible to ensure that there are enough metal ions to crosslink with the two-dimensional nanosheets. When the metal ion concentration is too low, there are insufficient crosslinking sites and insufficient connection between the two-dimensional nanosheets, which will lead to instability of the nanoconfined space structure and affect the performance of the composite material; and when the metal ion concentration is too high, metal ion aggregation will occur, which will destroy the orderly arrangement of the two-dimensional nanosheets and the uniformity of the nanoconfined space.
[0032] According to an embodiment of the present invention, the conductive polymer monomer is selected from at least one of aniline (An), pyrrole (Py), and 3,4-ethylenedioxythiophene (EDOT). Different conductive polymer monomers give different functional properties to the composite material. Polyaniline has good acid sensitivity and redox properties and can be used to prepare functional devices such as sensors; polypyrrole shows good biocompatibility in the biomedical field and can be applied to bioelectronic devices; poly (3,4-ethylenedioxythiophene) has a low electrochemical impedance and has advantages in the fields of electrochemical energy storage.
[0033] According to an embodiment of the present invention, the two-dimensional nanosheet is selected from at least one of montmorillonite (MMT) nanosheet, graphene oxide (GO) nanosheet, and MXene nanosheet. Montmorillonite nanosheet has high mechanical strength and modulus, can effectively enhance the mechanical properties of composite materials, improve the tensile and bending resistance of composite materials, and make composite materials more durable. Graphene oxide nanosheet has excellent mechanical properties, and its two-dimensional sheet structure can play a role in reinforcing the skeleton in the composite material, improve the overall strength and toughness of the composite material, and also improve the wear resistance of the composite material. MXene nanosheet has good mechanical properties and flexibility, which can make the composite material have better flexibility and processability while maintaining a certain strength, and is suitable for flexible electronic devices and other fields.
[0034] According to an embodiment of the present invention, the concentration of the two-dimensional nanosheets in the second mixed solution is 1~40mg / mL to ensure that a uniform and suitable density of two-dimensional nanosheet layers is formed on the surface of the liquid film, and a stable and suitable-sized nanoconfined space can be formed between adjacent two-dimensional nanosheets. This nanoconfined space is conducive to the orderly polymerization of conductive polymer monomers therein to form a regular structure, thereby improving the anisotropy of the composite material. When the concentration of the two-dimensional nanosheets is too low, the interaction between the two-dimensional nanosheets is weak, and an effective nanoconfined space and a stable network structure cannot be formed, resulting in the mechanical properties and conductive properties of the composite material cannot be fully improved; and when the concentration is too high, the two-dimensional nanosheets will agglomerate, destroying the uniformity and regularity of the nanoconfined space, and also affecting the performance of the composite material. When the two-dimensional nanosheets are montmorillonite nanosheets, the mass fraction of the montmorillonite nanosheets is preferably 1~4wt%; when the two-dimensional nanosheets are graphene oxide nanosheets, the concentration of graphene oxide nanosheets is preferably 1~3mg / mL; when the two-dimensional nanosheets are MXene nanosheets, the concentration of MXene nanosheets is preferably 2~6mg / mL.
[0035] According to an embodiment of the present invention, the mass ratio of the conductive polymer monomer to the two-dimensional nanosheet is 1~100:1. The appropriate mass ratio is conducive to the synergistic effect of the conductive polymer monomer and the two-dimensional nanosheet. The two-dimensional nanosheet provides a supporting platform with a high specific surface area for the conductive polymer monomer, which is conducive to the growth and orientation of the conductive polymer monomer, thereby improving the conductivity and stability of the composite material; at the same time, the conductive polymer monomer can also enhance the bonding force between the two-dimensional nanosheets and improve the mechanical properties of the composite material. By adjusting the mass ratio, the functional properties of the composite material can be regulated. When it is necessary to enhance the conductivity of the composite material, the proportion of the conductive polymer monomer can be appropriately increased; when there are higher requirements for the mechanical properties or barrier properties of the composite material, the proportion of the two-dimensional nanosheet can be relatively increased. This controllability enables the composite material to be customized according to different application scenarios and needs.
[0036] According to an embodiment of the present invention, the ratio of the concentration of the oxidant in the first mixed solution to the concentration of the conductive polymer monomer in the second mixed solution is 1 to 1.2:1, and the appropriate ratio helps to reduce the unreacted monomer or oxidant residue. If the oxidant concentration is too high, excessive oxidant will remain in the composite material, which will have a negative impact on the stability of the composite material, such as causing aging or degradation of the material; and if the oxidant concentration is too low, a large amount of unreacted conductive polymer monomers will remain, and these residual monomers will migrate or react during subsequent use, affecting the performance and stability of the composite material.
[0037] According to an embodiment of the present invention, the solvents used in the first mixed solution and the second mixed solution are independently selected from any one of N,N-dimethylformamide, dimethylsulfinamide, alcohol solvents, or N,N-dimethylformamide, dimethylsulfinamide, a mixture of alcohol solvents and water. Among them, alcohol solvents include ethanol, isopropanol, etc. Good solubility and dispersibility enable metal ions, conductive polymer monomers and two-dimensional nanosheets to be fully mixed and evenly distributed in the solution, and in the subsequent reaction and curing process, a more uniform composite material structure can be formed, reducing defects and inhomogeneities inside the composite material, and improving the overall performance and stability of the composite material.
[0038] According to an embodiment of the present invention, the temperature of the oxidative polymerization reaction is -5~5°C, and the time of the oxidative polymerization reaction is 0.5~1h. A lower reaction temperature can effectively reduce the reaction rate, making the oxidative polymerization reaction more stable and controllable. The drying temperature is 30~40°C, and the drying temperature is 2~4h. The drying temperature is relatively low, which can avoid the structural damage of the composite material caused by high temperature (greater than 40°C).
[0039] According to an embodiment of the present invention, the substrate is selected from any one of non-woven fabrics, filter membranes, filter paper, hydrogels, glass plates, silicon wafers, and mica sheets. When the substrate is selected from glass plates, silicon wafers, and mica sheets, the substrate is subjected to a lyophilic treatment to obtain a lyophilic surface. The lyophilic treatment is to change the surface of the material by physical or chemical methods to make it easier to contact with liquids, including: plasma treatment: using plasma to introduce lyophilic groups on the surface of the material; chemical coating: coating lyophilic chemicals, such as polyvinyl alcohol (PVA); surface grafting: grafting lyophilic groups on the surface through chemical reactions; ultraviolet light treatment: using ultraviolet light to introduce lyophilic groups on the surface; acid treatment: generating lyophilic groups on the surface through acid etching.
[0040] As a second aspect of the present invention, an anisotropic conductive nanocomposite material is provided, which is prepared by the above method.
[0041] In an embodiment of the present invention, an anisotropic conductive nanocomposite material having different conductive properties in different directions is prepared by the above method. By carrying out an oxidative polymerization reaction of a conductive polymer monomer and an oxidant in a nano-confined space, the growth and distribution of the conductive polymer monomer can be accurately controlled, so that the conductive properties of the composite material can be regulated according to the design in different directions, and more accurate anisotropic conductive properties can be achieved to meet the strict requirements of high-end electronic devices for conductive properties in specific directions and specific strengths. The nano-confined space is conducive to the formation of regular conductive channels by conductive polymer monomers, reducing electron scattering, thereby reducing the resistance of the composite material and improving its conductivity in a specific direction.
[0042] In the embodiment of the present invention, the thickness of the anisotropic conductive nano-composite material is 1-40 μm, so as to meet diverse application requirements and broaden the application scope of the anisotropic conductive nano-composite material.
[0043] As a third aspect of the present invention, there is provided an application of an anisotropic conductive nanocomposite material in an electronic device.
[0044] In the embodiments of the present invention, the anisotropic conductive nanocomposite material provided by the present invention has excellent conductivity in the horizontal direction, and is much greater than the conductivity in the vertical direction, and has broad application prospects in the fields of electrical connections, wearable electronic devices and sensors.
[0045] The present invention is further described below by examples and related test experiments. In the detailed description below, for ease of explanation, many specific details are set forth to provide a comprehensive understanding of the embodiments of the present invention. However, it is obvious that one or more embodiments may also be implemented without these specific details. And, in the absence of conflict, the details in the following embodiments may be combined into other feasible embodiments at will. All instruments, consumables and reagents in the following examples, if not otherwise specified, may be obtained from commercial sources.
[0046] Examples 1-3
[0047] In this embodiment 1-3, anisotropic conductive nanocomposites were prepared according to the raw material ratios shown in Table 1. The raw materials used in this embodiment 1-3 include pyrrole, montmorillonite (MMT) nanosheets and FeCl3. Among them, FeCl3 provides Fe ions and acts as an oxidant. Pyrrole monomer was purchased from Aladdin, CAS No.: 109-97-7; MMT nanosheets were purchased from nanocor, model PGW; FeCl3 was purchased from McLean, CAS No.: 7705-08-0.
[0048] Figure 2 is a flow chart for preparing the anisotropic conductive nanocomposite material in Example 1 of the present invention, as shown in Figure 2As shown, the specific preparation method is as follows.
[0049] (1) A 0.2M FeCl3 solution is prepared by using a dimethylformamide (DMF) / H2O mixed solvent with a volume ratio of 1:1. A nylon filter membrane with a lyophilic surface is provided (the amide groups on the surface of the nylon filter membrane make it hydrophilic, and the hydrophilicity of the nylon filter membrane can be enhanced by plasma treatment), and the above-mentioned 0.2M FeCl3 solution is added dropwise to form a liquid film 1 on the surface of the nylon filter membrane. A 2wt% MMT nanosheet is dispersed in a DMF / H2O solvent with a volume ratio of 1:1. Pyrrole is mixed evenly with 10ml of a 2wt% MMT nanosheet dispersion by shaking and ultrasound (5-10min). The above-mentioned pyrrole and MMT nanosheet mixture is poured on the surface of the liquid film 1 on the nylon filter membrane substrate in a 0°C environment.
[0050] (2) The MMT nanosheets (two-dimensional nanosheets 5) are super-spread and cross-linked and solidified by Fe ions (metal ions 3), forming a nano-confined space between the upper and lower adjacent MMT nanosheets parallel to the substrate. In the nano-confined space, pyrrole (conductive polymer monomer 4) and FeCl3 (oxidant 4) undergo an oxidative polymerization reaction, and a composite film is obtained after 0.5 h of reaction.
[0051] (3) The composite film was dried at 40 °C for 2 h to obtain an anisotropic conductive nanocomposite material.
[0052] Table 1 Raw material ratios of Examples 1-3
[0053]
[0054] Example 4
[0055] In this embodiment 4, an anisotropic conductive nanocomposite material was prepared, and the raw materials used included pyrrole, MMT nanosheets, CaCl2, and ammonium persulfate. Among them, pyrrole monomer (CAS No.: 109-97-7), CaCl2 (CAS No.: 10043-52-4), and ammonium persulfate (CAS No.: 7727-54-0) were purchased from Aladdin Company; MMT nanosheets were purchased from nanocor Company, model PGW. The specific preparation method is as follows.
[0056] (1) A mixed solution of 0.2M CaCl2 and 0.2M ammonium persulfate was prepared using a DMF / H2O mixed solvent with a volume ratio of 1:1. A nylon filter membrane with a lyophilic surface was provided, and the mixed solution was added dropwise to form a liquid film on the surface of the nylon filter membrane. MMT nanosheets with a mass fraction of 2wt% were dispersed using a DMF / H2O solvent with a volume ratio of 1:1. 1.2g of pyrrole was mixed with 10ml of a 2wt% MMT nanosheet dispersion by oscillation and ultrasound. The mixed solution of pyrrole and MMT nanosheets was poured onto the liquid film surface of the nylon filter membrane substrate at 0°C.
[0057] (2) The MMT nanosheets are super-spread and cross-linked and solidified by Ca ions, forming a nano-confined space between the upper and lower adjacent MMT nanosheets parallel to the substrate. Pyrrole and ammonium persulfate undergo oxidative polymerization reaction in the nano-confined space, and a composite film is obtained after 0.5 h of reaction.
[0058] (3) The composite film was dried at 40 °C for 2 h to obtain an anisotropic conductive nanocomposite material.
[0059] Example 5
[0060] In this embodiment 5, an anisotropic conductive nanocomposite material was prepared, and the raw materials used included pyrrole, graphene oxide (GO) nanosheets and FeCl3. Among them, pyrrole monomer was purchased from Aladdin Company, CAS number: 109-97-7; GO nanosheets were purchased from Gaoxin Company, model GO-1; FeCl3 was purchased from MacLean Company, CAS number: 7705-08-0. The specific preparation method is as follows.
[0061] (1) A 0.2M FeCl3 solution was prepared using a DMF / H2O mixed solvent with a volume ratio of 1:1. A nylon filter membrane with a lyophilic surface was provided, and the above-mentioned 0.2M FeCl3 solution was added dropwise to form a liquid film on the surface of the nylon filter membrane. GO nanosheets with a concentration of 2mg / ml were dispersed using a DMF / H2O solvent with a volume ratio of 1:1. 1.2g of pyrrole was mixed with 10ml of a 2mg / ml GO nanosheet dispersion by oscillation and ultrasound. The above-mentioned pyrrole and GO nanosheet mixture was poured onto the liquid film surface of the nylon filter membrane substrate in a 0°C environment.
[0062] (2) The GO nanosheets were super-spread and cross-linked and solidified by Fe ions, forming a nano-confined space between the upper and lower adjacent GO nanosheets parallel to the substrate. Pyrrole and FeCl3 underwent oxidative polymerization reaction in the nano-confined space, and a composite film was obtained after 0.5 h of reaction.
[0063] (3) The composite film was dried at 40 °C for 2 h to obtain an anisotropic conductive nanocomposite material.
[0064] Example 6
[0065] In this Example 6, an anisotropic conductive nanocomposite material was prepared, and the raw materials used included aniline, MMT nanosheets and FeCl3. Among them, aniline monomer was purchased from Aladdin Company, CAS No.: 62-53-3; GO nanosheets were purchased from Gaoxin Company, model GO-1; FeCl3 was purchased from McLean, CAS No.: 7705-08-0. The specific preparation method is as follows.
[0066] (1) A 0.2M FeCl3 solution was prepared using a DMF / H2O mixed solvent with a volume ratio of 1:1. A nylon filter membrane with a lyophilic surface was provided, and the above-mentioned 0.2M FeCl3 solution was added dropwise to form a liquid film on the surface of the nylon filter membrane. MMT nanosheets with a mass fraction of 2wt% were dispersed using a DMF / H2O solvent with a volume ratio of 1:1. 1.2g of aniline was mixed with 10ml of a 2wt% MMT nanosheet dispersion by oscillation and ultrasound. The above-mentioned aniline and MMT nanosheet mixture was poured onto the liquid film surface of the nylon filter membrane substrate in an environment of 0°C.
[0067] (2) The MMT nanosheets were super-spread and cross-linked and solidified by Fe ions, forming a nano-confined space between the upper and lower adjacent MMT nanosheets parallel to the substrate. Aniline and FeCl3 underwent oxidative polymerization reaction in the nano-confined space, and a composite film was obtained after 0.5 h of reaction.
[0068] (3) The composite film was dried at 40 °C for 2 h to obtain an anisotropic conductive nanocomposite material.
[0069] Comparative Example 1
[0070] In this comparative example 1, a conductive nanocomposite material was prepared, and the raw materials used included pyrrole, MMT nanosheets and ammonium persulfate. Among them, pyrrole monomer (CAS No.: 109-97-7) and ammonium persulfate (CAS No.: 7727-54-0) were purchased from Aladdin Company; MMT nanosheets were purchased from nanocor Company, model PGW. The specific preparation method is as follows.
[0071] (1) DMF / H2O solvent with a volume ratio of 1:1 was used to disperse MMT nanosheets with a mass fraction of 2 wt%.
[0072] (2) 1.2 g of pyrrole and 0.2 M ammonium persulfate were mixed with 10 ml of 2 wt % MMT nanosheet dispersion by shaking and ultrasound.
[0073] (3) The mixed solution of pyrrole, ammonium persulfate and MMT nanosheets was cast into a mold and reacted at 0°C for 0.5 h to obtain a composite film.
[0074] (4) Dry the composite film at 40 °C for 2 h to obtain a conductive nanocomposite material.
[0075] The difference between Comparative Example 1 and Example 4 is that a conventional casting method is adopted, that is, the reaction solution is directly poured into a 10 cm×10 cm mold, and finally dried at 40° C. to prepare the MMT / PPy conductive nanocomposite material.
[0076] Furthermore, the composite materials obtained in the above examples and comparative examples were subjected to structural characterization and performance testing.
[0077] The structure of the anisotropic conductive nanocomposite material in Example 1 was characterized by scanning electron microscopy (SEM). Specifically, the anisotropic conductive composite material was cooled with liquid nitrogen for 0.5-1 h, and the cross-section obtained by impact fracture was observed by scanning electron microscopy at an acceleration voltage of 20 KV. Figure 3 This is a scanning electron microscope image of the anisotropic conductive nanocomposite material in Example 1 of the present invention at a magnification of 5000×; Figure 4 This is a scanning electron microscope image of the anisotropic conductive nanocomposite material in Example 1 of the present invention at a magnification of 10000×.
[0078] from Figure 3 and Figure 4 It can be seen that the composite material presents a distinct layered structure with certain gaps and boundaries between the layers. This verifies the super-spreading of the two-dimensional nanosheets and the polymerization of the conductive polymer monomers in the nano-confined space during the preparation process. That is, the MMT nanosheets are oriented and arranged through super-spreading to form an ordered multilayer structure, and polypyrrole polymerizes and grows between the MMT layers.
[0079] In order to further prove that pyrrole aggregates in the nanoconfined space formed by MMT nanosheets, transmission electron microscopy (TEM) and X-ray diffraction (XRD) were used to test the changes in the interlayer spacing of MMT nanosheets. Figure 5 This is a transmission electron microscope image of the anisotropic conductive nanocomposite material in Example 1 of the present invention; Figure 6 This is the X-ray diffraction pattern of the anisotropic conductive nanocomposite material in Example 1 of the present invention.
[0080] like Figure 5 As shown in Figure 2, the orderly arrangement of MMT nanosheets can be seen, and layered PPy crystal regions are formed between the neatly arranged nanosheets. Figure 6 As shown in the figure, due to the incorporation of PPy, the diffraction peak of the anisotropic conductive nanocomposite in Example 1 shifts from 6.1° to 4.6°, indicating that PPy is successfully synthesized between the MMT nanosheets. Figure 5 The change in interlamellar spacing is a strong evidence for the successful embedding of PPy into the MMT layer.
[0081] Figure 7 This is the X-ray diffraction pattern of the anisotropic conductive nanocomposite material in Example 5 of the present invention.
[0082] like Figure 7 As shown, it can be found that the diffraction peak of the anisotropic conductive nanocomposite material in Example 5 moves from 10.8° to 9.3°, and the interlayer spacing becomes larger, indicating that PPy is successfully synthesized between the GO nanosheet layers.
[0083] Figure 8 Schematic diagram of the conductivity test in the horizontal direction in the embodiment of the present invention. The specific test method is: four-electrode (four-probe) method. Silver paste is used to make electrodes at both ends of the sample. The conductivity in the horizontal direction is calculated by formula (1)-(3).
[0084] (1);
[0085] (2);
[0086] (3).
[0087] Wherein, S is the cross-sectional area of the test sample, H is the width of the test sample, D is the thickness of the test sample, R is the test resistance, L is the distance between the positive and negative electrodes, ρ is the resistivity of the test sample, and σ is the conductivity of the test sample.
[0088] Fig. 9 Schematic diagram of the conductivity test in the vertical direction in the embodiment of the present invention. The specific test method is: four-electrode (four-probe) method. The electrode material is copper foil. The conductivity in the vertical direction is calculated by formula (4)-(6).
[0089] (4);
[0090] (5);
[0091] (6).
[0092] Where S is the test sample area, Pi is π, r is the test sample radius, R is the test resistance, L is the distance between the positive and negative electrodes, ρ is the test sample resistivity, and σ is the test sample conductivity.
[0093] pass Figure 8 and Fig. 9 The conductivity of the anisotropic conductive nanocomposite materials in the above embodiments and comparative examples in different directions was tested by the method shown. The test results are shown in Table 2.
[0094] Table 2 Conductivity of anisotropic conductive nanocomposites in different directions in Examples 1-6 and Comparative Example 1
[0095]
[0096] It can be found from Table 2 that the horizontal conductivity and vertical conductivity of the embodiments are much higher than those of the comparative example 1 as a whole. Taking the horizontal conductivity as an example, the horizontal conductivity of the embodiments 1-3 is in the range of 2.37-3.93 S / cm, and the horizontal conductivity of the embodiments 4-6 is lower, but still within 10 -6 -10 -7 S / cm level, while the horizontal conductivity of comparative example 1 is only 1.8499×10 -9 S / cm, which shows that the composite material in the embodiment is significantly better than the composite material in comparative example 1 in terms of electrical conductivity. For Examples 1-3, the horizontal conductivity is much higher than the vertical conductivity, and the difference between the two is 3-5 orders of magnitude, showing that the material has obvious anisotropic conductive properties. Examples 4-6 also embody this anisotropy. Although the absolute values of their horizontal and vertical conductivities are relatively low, the horizontal conductivity is still higher than the vertical conductivity. This is because, under the action of the shear liquid flow, the two-dimensional nanosheets are oriented in a direction parallel to the liquid film, and are cross-linked and solidified by metal ions. In the direction perpendicular to the liquid film, a nano-confined space is formed between adjacent two-dimensional nanosheets, and an oxidative polymerization reaction occurs between the conductive polymer monomer and the oxidant in the nano-confined space, thereby obtaining an anisotropic conductive nanocomposite material. Specifically, in the direction parallel to the liquid film, the conductive polymer material undergoes an oxidative polymerization reaction between the upper and lower two-dimensional nanosheets, so that the conductive nanocomposite material has good conductivity in the direction parallel to the liquid film; at the same time, due to the poor conductivity of the two-dimensional nanosheets used, the upper and lower two-dimensional nanosheets are hindered, so that the conductive nanocomposite material has poor conductivity in the direction perpendicular to the liquid film. In the comparative example, the MMT nanosheet layers are randomly stacked to form a disordered structure. The PPy molecules are randomly distributed between the MMT nanosheet layers or on the surface, resulting in discontinuity of the conductive path in both the horizontal and vertical directions. The electron transmission needs to cross more interfaces or insulating MMT nanosheet layers, resulting in low conductivity, even more in the vertical direction, and the structure of ordinary casting is relatively loose, with more interface defects and pores, which hinders the continuity of the conductive path. However, due to the super-spreading of the liquid film surface, the distance between the two-dimensional nanosheet layers is more uniform, so that the conductive path of the conductive nanocomposite material in the embodiment in the vertical direction is better than that of comparative example 1.
[0097] The specific embodiments described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A method for preparing an anisotropic conductive nanocomposite material, characterized in that: include: applying a first mixed solution containing metal ions and an oxidant on a substrate having a lyophilic surface to form a liquid film on the lyophilic surface; pouring a second mixed liquid formed by uniformly mixing a conductive polymer monomer and a two-dimensional nanosheet dispersion liquid onto the surface of the liquid film and allowing the mixture to stand for a period of time, wherein the two-dimensional nanosheets are super-spread on the surface of the liquid film and form nano-confined spaces between adjacent two-dimensional nanosheets, and within the nano-confined spaces, the conductive polymer monomer and the oxidant undergo an oxidative polymerization reaction to obtain a composite film; The composite film is dried to obtain an anisotropic conductive nanocomposite material.
2. The preparation method according to claim 1, characterized in that: The two-dimensional nanosheets are super-spread on the surface of the liquid film and a nano-confined space is formed between adjacent two-dimensional nanosheets, which comprises: The two-dimensional nanosheets are super-spread on the surface of the liquid film and oriented in a first direction, and then the metal ions are cross-linked and solidified with the two-dimensional nanosheets to form nano-confined spaces between adjacent two-dimensional nanosheets in a second direction; The first direction is parallel to the substrate, and the second direction is perpendicular to the substrate.
3. The preparation method according to claim 1, characterized in that: The metal ion is selected from at least one of iron ion, calcium ion and aluminum ion; The oxidant is selected from at least one of hydrogen peroxide, dichromate, persulfate, and ferric chloride; The concentration of metal ions in the first mixed solution is 0.2-3 mol / L.
4. The preparation method according to claim 1, characterized in that: The conductive polymer monomer is selected from at least one of aniline, pyrrole, and 3,4-ethylenedioxythiophene; The two-dimensional nanosheet is selected from at least one of montmorillonite nanosheet, graphene oxide nanosheet, and MXene nanosheet; The concentration of the two-dimensional nanosheets in the second mixed solution is 1-40 mg / mL.
5. The preparation method according to claim 4, characterized in that: The mass ratio of the conductive polymer monomer to the two-dimensional nanosheet is 1-100:1; The ratio of the concentration of the oxidant in the first mixed solution to the concentration of the conductive polymer monomer in the second mixed solution is 1-1.2:
1.
6. The preparation method according to claim 1, characterized in that: The solvents used in the first mixed solution and the second mixed solution are independently selected from any one of N,N-dimethylformamide, dimethylsulfinamide, alcohol solvents, or a mixture of N,N-dimethylformamide, dimethylsulfinamide, alcohol solvents and water.
7. The preparation method according to claim 1, characterized in that: The temperature of the oxidative polymerization reaction is -5 to 5°C, and the time of the oxidative polymerization reaction is 0.5 to 1 hour.
8. The preparation method according to claim 1, characterized in that: The substrate is selected from any one of non-woven fabrics, filter membranes, filter paper, hydrogels, glass plates, silicon wafers, and mica sheets; When the substrate is selected from a glass plate, a silicon wafer, or a mica sheet, the substrate is subjected to a lyophilic treatment to obtain a lyophilic surface.
9. An anisotropic conductive nanocomposite material, characterized in that: The method is prepared by the method described in any one of claims 1 to 8.
10. Use of the anisotropic conductive nanocomposite material according to claim 9 in electronic devices.
Citation Information
Patent Citations
Graphene / polypyrrole electromagnetic shielding film and preparation method thereof
CN105062064A
Preparation method of porous composite nanofilm material
CN108467502A
Flexible self-supporting anisotropic electrochromic polyaniline film, preparation method thereof and electrochromic device
CN112920406A
Electroconductive woven and non-woven fabric and method of manufacturing thereof
US20070054577A1
Textured film and production method thereof
WO2024112275A1